2006
DOI: 10.1007/s10519-005-9020-0
|View full text |Cite
|
Sign up to set email alerts
|

High Heritability of Speech and Language Impairments in 6-year-old Twins Demonstrated Using Parent and Teacher Report

Abstract: Previous twin studies have demonstrated high heritability of specific language impairment (SLI) when the diagnosis is based on psychometric testing. The current study measured the effectiveness of parent and teacher ratings of communication skills in identifying heritable language impairment. The Children's Communication Checklist was completed by parents and teachers of 6-year-old twins recruited from a general population sample. One hundred and thirty twin pairs (65 MZ) were selected because at least one twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 19 publications
4
50
0
3
Order By: Relevance
“…The disorder is highly heritable [5] but genetic contributions are expected to be complex in nature with significant heterogeneity between individuals [6]. Common risk variants within ATP2C2 (OMIM#613082), CMIP (OMIM#610112) [7], ABCC13 (OMIM#608835) [8], FLNC (OMIM#102565), RBFOX2 (OMIM#612149) [9] and ROBO2 (OMIM#602431) [10] have been associated with quantitative measures of language skills.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder is highly heritable [5] but genetic contributions are expected to be complex in nature with significant heterogeneity between individuals [6]. Common risk variants within ATP2C2 (OMIM#613082), CMIP (OMIM#610112) [7], ABCC13 (OMIM#608835) [8], FLNC (OMIM#102565), RBFOX2 (OMIM#612149) [9] and ROBO2 (OMIM#602431) [10] have been associated with quantitative measures of language skills.…”
Section: Introductionmentioning
confidence: 99%
“…Language impairments can include those involving semantics, such as subtle nuances, as well as pragmatic aspects of language in a social context [1]. Twin studies have suggested that, although children must be exposed to language in their environment in order to learn it, communication impairments have a major heredity component [2,3]. However, the low estimates of environmental influences may be misleading for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher reports of language skills would be particularly useful as the informants usually have a large “reference base” for comparison, from years of experience with children of the same age, representing the full range of language skills. Teacher reports provide information about language skills that may be challenging to elicit in a test situation with young preschoolers due to shyness and/or limited motivation or attention [13] and they are easy and inexpensive to administer.…”
Section: Introductionmentioning
confidence: 99%